CONSTRUCTIVE MODELLING FOR ZONE OF RECOVERY ENERGY DISTRIBUTION OF DC TRACTION - Shynkarenko, V. I.; Sablin, O. I.; Ivanov, O. P. (Science and Transport Progress, 2016)
Purpose.The article is aimed to develop the means and methods of forming a plurality of real and potential structural diagrams for zones of energy recovery and different locations of trains for further training neuro-fuzzy networks on the basis of expert solutions and also for the formation of good control. Methodology. Methodology of mathematical and algorithmic constructivism for modeling the structural diagrams of the electric supply system and modes of traction power consumption and the train’s locations in zones of energy recovery was applied. This approach involves the development of constructive-synthesizing structures (CSS) with transformation by specialization, interpretation, specification and implementation. Development CSS provides an extensible definition media, relations and the signature of operations and constructive axiomatic. The most complex and essential part of the axioms is the set formed by the substitution rules defining the process of withdrawal of the corresponding structures. Findings. A specialized and specified CSS, which allows considering all the possibilities and features, that supply power traction systems with modern equipment, stations and trains location was designed. Its feature: the semantic content of the terminal alphabet images of electrical traction network and power consumers with relevant attributes. A special case of the formation of the structural diagram shows the possibilities CSS in relation to this problem. Originality. A new approach to solving the problem of rational use of energy recovery, which consists in application of the methods and means of artificial neural networks, expert systems, fuzzy logic and mathematical and algorithmic constructivism. This paper presents the methods of constructive simulation of a production-distribution of energy recovery zone structure in the system of the DC traction. Practical value. The tasks decision of the rational use of energy recovery can significantly save energy, contribute to the technical re-equipment of a railway transportation of Ukraine through the introduction of modern means and capabilities. The developed model can be used to solve other energy-saving tasks in different systems of electric transport.